Trade Facilitation for Global and Regional Value Chains in SACU - World Bank Group (World Bank, Washington, DC, 2016)
In this context, this note summarizes the findings of a recent World Bank, SACU Secretariat assessment of regional trade facilitation based on the Trade and Transport Facilitation Assessment (TTFA) methodology. The assessment looks at regional trade facilitation through the lens of value chains, with the objective to understand how the region’s trade and transport environment could be improved to facilitate more extensive and deeply integrated regional trade, linked to competitive participation in global value chains. The remainder of this note is structured as follows: section two provides a brief overview of regional trade and freight flows. This is followed in section three by a brief review of the trade and transport environment (including infrastructure and policy) across each SACU member state. Section four summarizes the findings of the detailed analysis, from a trade facilitation perspective, of the regional value chains in four key industry sectors: agro-processing; agro-processing; automotive; beef; and textiles/apparel. Section five then focuses on identifying potential solutions to three key trade and transport facilitation challenges identified through the value chain assessments. Finally, section six concludes.